Processing trade, domestic and foreign firms, and the differential impact of the Great Recession: Evidence from Chinese customs data - Roy, Devesh; Tian, Xi (2019)
Using firm-level transaction records from the proprietary Chinese Customs data we estimate differential impacts of the Great Recession (GR) of 2008-09 on exports of private domestic firms (PDFs) and foreign invested firms (FIFs). We exploit the longitudinal nature of the data spanning almost a decade (2003-2011), as well as product level details available in the customs data, to establish causal links. We identify processing trade intensity as one possible mechanism of the fall in exports due to the GR, as well as the slow recovery in its aftermath. Prior to the GR, the FIFs not only were more involved with processing trade compared to the PDFs but also accounted for the larger share of China’s exports. Subsequently, the firms with greater processing trade intensity suffered more due to the GR. We argue that processing trade of the FIFs captured the transmission of the negative demand shocks of the GR.